Optical properties of zinc oxide thin films fabricated via radio frequency magnetron sputtering for optical hydrogen gas sensor application - Mustaffa, Siti Nor Aliffah (2017)
This thesis focused on the optimization of zinc oxide (ZnO) thin films for optical hydrogen (H2) gas sensor using radio frequency (RF) magnetron sputtering technique. Various strategies were adopted to produce optically controlled thin films with the desired properties. This work focused on the effect of deposition parameters that included deposition time, RF power, argon/oxygen (Ar/O2) gas percentage, and annealing condition on thin film thickness, surface roughness, crystal phase, phonon modes, and optical band gap. The thin films‟ surface morphology and thickness were characterized carefully using atomic force microscopy (AFM) and surface profilometry, respectively, while crystallographic structure was examined using X-ray diffraction (XRD). Ultraviolet visible spectroscopy (UV-VIS) was used to investigate the optical transmittance and band gap of the produced films. Fourier transforms infrared spectroscopy (FTIR) was performed to examine the functional group, while Raman spectroscopy was used to characterize the phonon modes. Deposition time was found to have a very significant effect on thin film thickness, where the thicker thin film obtained when deposited for 180 min was 851.35 ± 4.45 nm. XRD analysis confirmed that RF power of 150 W with influence of post-deposition annealing was able to promote growth of crystal structure with crystal plane orientation of (002) as hexagonal wurtzite structure. Furthermore, increasing the RF power from 50 to 150 W also reduced the surface roughness from 88.2 to 6.86 nm. In order to improve the optical properties, O2 gas percentage was reduced from 50% to 4%. However, there was an existence of diffraction peak at (011) plane despite improving the intensity of diffraction peak at plane (002) at 4% of O2 gas percentage. This was due to O2 atoms that induced the breaking and reforming of Zn-O bonds, which could modify the ZnO bonding network. Finally, optimized ZnO thin films were successfully deposited with RF power of 150 W and 4% of O2 gas percentage for 180 min. It was found that Raman active phonon modes for the optimized ZnO thin films were at E2 (high) and A1 (LO) which were 440 and 565 cm-1, respectively. The FTIR analyses showed that ZnO absorption bands in the fingerprint region between 500-450 cm-1 had arisen from inter-atomic vibrations due to stretching of Zn-O bond. Hence, the optimized ZnO thin films were tested for H2 optical sensing application. At the operating temperature of 27 oC with concentration of H2 gas at 2 mol%, it was found that gas sensing characteristic of novel RF-sputtered ZnO thin film was strongly influenced by crystalline at the size of 124.10 nm, thickness of 399.43 ± 1.47 nm and surface roughness of 18.9 nm. The gas sensing mechanism of the novel RF-sputtered ZnO thin film was based on the surface reaction between adsorbed oxygen and the H2 gas where more oxygen was chemisorbed in the form of O2-, O-, and O2- by ZnO thin film. The calculated molar absorptivity, ε increased with the increase of rms surface roughness whereby relatively high surface roughness is better to optically absorb H2 gas.